Efforts To Stabilize Children's Mental Health Through Screening The Use Of Gadgets In Children In The Pandemic Period Of Covid-19 - Zuhro, Dyah Fauzia (Journal of Public Health Science Research (JPHSR), 2020)
The development of the industrial era 4.0 made various changes in community activities.One of them is theuse of Gadgeteveryday that when it had become a necessity. Use of the wise tentunyaakan bring the impact that good and helpful. But otherwise Especially again when it the people of old let children use gadgets without supervision. According to a study at the Chinese Academy of Science, it turns out that addiction to gadgets and the internet can change a person's brain structure. Brain development in children during their infancy needs attention. Given the high intensity of use of gadgets in almost most major activity of children. It is an impact on the production of the hormone dopamine, which exaggerated disrupt maturation function of the prefrontal cortex that controls emotions, control themselves, bear responsibility, decision -making and the values of moral others. Addiction to gadgets can cause interference pemusat attention and hyperactivity .